2023
DOI: 10.31026/j.eng.2013.12.05
|View full text |Cite
|
Sign up to set email alerts
|

Forward Osmosis Process for the Treatment of Wastewater from Textile Industries

Abstract: This paper was aimed to study the efficiency of forward osmosis (FO) process as a new application for the treatment of wastewater from textile effluent and the factors affecting the performance of forward osmosis process.The draw solutions used were magnesium chloride (MgCl2), and aluminum sulphate (Al2 ( SO4)3 .18 H2O), and the feed solutions used were reactive red, and disperse blue dyes.Experimental work were includes operating the forward osmosis process using thin film composite (TFC) membrane as flat she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The similar Jw obtained with the different dyes used (Remazol turquoise G-133% and Sirius Blue K-CFN) in the tests with MS1 and MS2 may be related to the molecular weight of the substances, as Makki et al [59] observed in a study on the concentration of different dyes (Disperse Blue and Reactive Red) by means of FO also using a CTA membrane. They observed that for two types of FS with the same concentration, the permeate flux is limited by the molecular weight of the substances that compose it.…”
Section: Influence Of the Type Of Dye On The Concentration Efficiencysupporting
confidence: 63%
“…The similar Jw obtained with the different dyes used (Remazol turquoise G-133% and Sirius Blue K-CFN) in the tests with MS1 and MS2 may be related to the molecular weight of the substances, as Makki et al [59] observed in a study on the concentration of different dyes (Disperse Blue and Reactive Red) by means of FO also using a CTA membrane. They observed that for two types of FS with the same concentration, the permeate flux is limited by the molecular weight of the substances that compose it.…”
Section: Influence Of the Type Of Dye On The Concentration Efficiencysupporting
confidence: 63%